NEW BRANDING TECHNOLOGIES THAT TRIGGER BRAND ENGAGEMENT. BRANDING PRACTICES IN THE FMCG MARKET IN RUSSIA (Revista Inclusiones, 2021)
The article examines one of the innovative technologies for branding FMCG goods as one of thetechniques of value emotation. The relevance of the study is due to the high level of competition inthe segment and the complexity of brand differentiation both at the functional and rational level, andat the emotional level. The impulse emotional response to the brand's product, which is of particularimportance in the segment, is becoming more difficult and standard branding techniques do notalways succeed. This article provides an analysis of the cases of the leaders of the FMCG marketand agencies, the profile of which is the development of visual brand communication in order toidentify technologies that can solve the problem of emotional brand differentiation in the most effectiveway. The results of the study show that the most promising is the storytelling technology in branding,which carries out a targeted impact on the consumer if the storytelling is omnichannel - telling a storyboth verbally and visually.